Informe de mantenimiento y estudio estadístico del desgaste de las llantas de los carros recolectores de basura de las empresas varias de Medellín. (2011)
Mechanical engineering has to be at par to do studies in the maintenance departments of the industry either industry or transportation. Empress varies de Medellin (EEVVM) is a company of public sector dedicated to transportation and collection of garbage from Medellin city and five townships, (Santa Helena, Palmitas, san Antonio de Prado, san Cristobal and Belen AltaVista). It a two administrative headquarter and the base of operations and maintenance. The garage is ubicated in the north of the city, where they perform corrective and preventive maintenance. Keeping the operation of empresas varias de Medellin is the most important, since their production depends on it, which is why the maintenance department been keeping records since 2008. About all maintenance being done to vehicles, but not only this, it also keeps track of fuel consumption since tires are the main expense in the maintenance area. But work does not and with bringing a database with information, but also ensuring that the work being done to vehicles has been implemented correctly and in due time. About tire control; this is a topic, that has not taken any action to improve the database and it is not enough to control just the tires that are operational, but also records of income and movements in each vehicle. The work of the auditor responsible for checking the tires to ensure the good condition of these throughout the fleet, and supervise the erection and dismantling.